If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 1 + 7(-3 + -7x) = -4x + 25 1 + (-3 * 7 + -7x * 7) = -4x + 25 1 + (-21 + -49x) = -4x + 25 Combine like terms: 1 + -21 = -20 -20 + -49x = -4x + 25 Reorder the terms: -20 + -49x = 25 + -4x Solving -20 + -49x = 25 + -4x Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '4x' to each side of the equation. -20 + -49x + 4x = 25 + -4x + 4x Combine like terms: -49x + 4x = -45x -20 + -45x = 25 + -4x + 4x Combine like terms: -4x + 4x = 0 -20 + -45x = 25 + 0 -20 + -45x = 25 Add '20' to each side of the equation. -20 + 20 + -45x = 25 + 20 Combine like terms: -20 + 20 = 0 0 + -45x = 25 + 20 -45x = 25 + 20 Combine like terms: 25 + 20 = 45 -45x = 45 Divide each side by '-45'. x = -1 Simplifying x = -1
| W+2=150 | | x^2y+7x-18y= | | f(1)=3+2(1) | | 4x-10=86+2x | | 0.7=1.1 | | W-2=150 | | -2(2-4b)=16+3b | | 20w-18=15w+90 | | tanx=2.75 | | 1(j+1)=5(j-3) | | 5/3*-10/9 | | 3(x-5)2=9 | | 6.5+k=17 | | 7x-3=61 | | 1=2x+2x-3 | | 4/7x21 | | 7k+26=25 | | (-6x)-(32)=2x | | x-7/5=2/3 | | hx=x^2+3x-7 | | q+(-23)=-3 | | -6x-(32)=2x | | -18=-6(r-90) | | -3-1/5x=7 | | 5.4+n=10 | | (4)2-4(-5)-1= | | 38=6x+2x-2 | | p/3-12=0 | | m-4/5=1/5 | | (x^2/2r^3)^5 | | 2(x-9)=4(x+-5) | | 72=6(v+5) |